a) Ta có A = 4x2 - 4x + 1 = (2x - 1)2 \(\ge0\forall x\)
Dấu "=" xảy ra <=> 2x - 1 = 0 => x = 0,5
Vậy GTNN của A là 0 khi x = 0,5
b) Ta có x2 + 4y2 + 4xy = x2 + 2xy + 2xy + 4y2 = x(x + 2y) + 2y(x + 2y) = (x + 2y)2 \(\ge0\forall x;y\)
Dấu "=" xảy ra <=> x + 2y = 0 => x = - 2y
Vậy GTNN của B là 0 khi x = -2y
a) 4x2 - 4x + 1 = ( 2x - 1 )2 ≥ 0 ∀ x
Đẳng thức xảy ra <=> 2x - 1 = 0 => x = 1/2
Vậy GTNN của biểu thức = 0 <=> x = 1/2
b) x2 + 4y2 + 4xy = ( x + 2y )2 ≥ 0 ∀ x ,y
Đẳng thức xảy ra <=> x + 2y = 0 => x = -2y
Vậy GTNN của biểu thức = 0 <=> x = -2y
A) \(4x^2-4x+1\)
\(=\left(2x-1\right)^2\ge0\)
Min = 0 \(\Leftrightarrow2x-1=0\Leftrightarrow x=\frac{1}{2}\)
B) \(x^2+4y^2+4xy\)
\(=\left(x+2y\right)^2\ge0\)
Min = 0 \(\Leftrightarrow x+2y=0\)
\(\Leftrightarrow x=-2y\)
a ) \(A=4x^2-4x+1\)
\(\Rightarrow A=x^2-4x+4-3\)
\(\Rightarrow A=\left(x-2\right)^2-3\)
Do \(\left(x-2\right)^2\ge0\)với \(\forall x\)( dấu '=' xảy ra \(\Leftrightarrow x-2=0\Rightarrow x=2\))
\(\Rightarrow\left(x-2\right)^3-3\ge-3\)( dấu '=' xảy ra \(\Leftrightarrow x=2\))
Vậy \(A_{min}=-3\)tại \(x=2\)